Research on the Cloud Computing in Online Charging System Application - Hong Hu; Na Chen; Jinjuan Zhang; Xinyi Xu (Dianxin kexue)
The characters and challenges of online charging system were analyzed,and the cloud computing application in online charging system was studied.Finally,the application and programs on online charging system were put forward,also the future research of cloud computing was expected.